Rebuilding customer trust after cyberattacks: Examining the role of trust recovery in Indonesian Islamic digital banking - Nurrizkiana, Dinda Dwi; Afifudin, Afifudin; Alrasyid, Harun (University of Islam Malang, 2025)
The increasing reliance on digital platforms in Islamic banking has heightened customers’ vulnerability to cyberattacks, making post-crisis trust management a strategic priority. However, limited research has examined how trust can be effectively restored after such incidents. This study investigates the direct and indirect effects of system security, communication, and reputation on customer trust, with trust recovery as a mediating variable. A quantitative explanatory design was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze data from 252 users of an Islamic digital banking institution in Indonesia affected by a major cyberattack in 2023. The results reveal that system security, communication, and reputation do not directly influence customer trust but become significant when mediated by trust recovery. These findings indicate that customers place greater value on tangible recovery efforts than on pre-crisis institutional claims. This suggests that trust is not restored through declarative assurances alone but rather through demonstrable recovery actions that signal institutional competence and commitment. By integrating Islamic based ethical principles such as amanah (responsibility), itqan (professionalism), and transparency into recovery strategies, this study extends trust recovery theory in the context of Islamic digital services.